2020
DOI: 10.1111/jonm.13111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of WeChat‐based 'three good things' on turnover intention and coping style in burnout nurses

Abstract: Turnover intention is broadly considered as a person's intention to leave their current job and find another, followed through by resigning (Bedeian & Armenakis, 1981). As a description of one's desire to withdraw from an organisation, turnover intention strongly correlates with burnout (Choi & Lee, 2017). Helnen et al. (2013) conducted a multicountry, multicentre, cross-sectional study in which 23,159 nurses from 10 European countries completed anonymous questionnaires. They found that 5%-17% of nurses intend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…Stress‐coping strategies are behavioural approaches taken by individuals to deal with stress through modulating their physiology and emotion and reducing discomfort (Brambila‐Tapia et al, 2022; Deklava et al, 2014; Guo et al, 2020). Prior findings showed that nurses adopt various coping strategies when suffering from occupational stress (Hasan et al, 2018; Kim & Kim, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Stress‐coping strategies are behavioural approaches taken by individuals to deal with stress through modulating their physiology and emotion and reducing discomfort (Brambila‐Tapia et al, 2022; Deklava et al, 2014; Guo et al, 2020). Prior findings showed that nurses adopt various coping strategies when suffering from occupational stress (Hasan et al, 2018; Kim & Kim, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study's findings revealed that nurses' turnover intentions were positively correlated with burnout; the higher the degree of burnout was, the more likely they were to leave, similar to the results of existing studies ( 70 , 71 ). Therefore, managers should monitor nurses' physical and emotional symptoms and establish emotional and social support networks ( 72 ), such as the Three Good Things based on WeChat ( 73 ), to improve nurses' psychological wellbeing and thus stabilize the nursing workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence indicated that sufficient attention should be given to younger nurses who frequently work night shifts and have less supervisory support. Scientific scheduling system, a harmonious organizational atmosphere, rational allocation of human resources, and programs that have been confirmed to improve emotion regulation and coping capacity, such as coping skills, training, and regular psychological guidance, should also be considered by organizations ( Medisauskaite and Kamau, 2019 ; Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%